Sustained elevation of MG53 in the bloodstream increases tissue regenerative capacity without compromising metabolic function - Zehua Bian (Nature Portfolio, 2019)
MG53 is a protein that regulates the cell membrane repair process, and it’s been suggested that it might play a role in diabetes. Here, the authors demonstrate that circulating MG53 functions as a myokine to facilitate tissue injury-repair and regeneration without impacting glucose handling.